2006
DOI: 10.1038/sj.npp.1301254
|View full text |Cite
|
Sign up to set email alerts
|

Strain Differences in Lithium Attenuation of d-Amphetamine-Induced Hyperlocomotion: A Mouse Model for the Genetics of Clinical Response to Lithium

Abstract: Lithium attenuation of stimulant-induced hyperlocomotion is a rodent model that may be useful both to understand the mechanism of the therapeutic action of lithium and to develop novel lithium-mimetic compounds. To lay the foundation for future investigations into the neurobiology and genetics of lithium as a therapeutic agent, we studied the effect of lithium on d-amphetamine-induced hyperlocomotion in 12 (3 outbred) mouse strains. In our initial screening, mice received either (1) no drugs, (2) LiCl only, (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
82
2
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(92 citation statements)
references
References 45 publications
7
82
2
1
Order By: Relevance
“…However, brain lithium levels ( Figure 1b) were significantly different among groups: F(2, 23) = 62.53, p < 0.0001. This is consistent with the finding from numerous groups that establishment of steady-state brain lithium levels in the rodent brain lags behind serum lithium levels (Ghoshdastidar et al, 1989;Gould et al, 2007b;Morrison et al, 1971). Bersudsky and colleagues recently reported that the effect of lithium in the FST after long-term treatment requires serum levels above 0.8 mM (Bersudsky et al, 2007).…”
Section: Experiments 1: Determination Of Brain and Serum Lithium Levelssupporting
confidence: 91%
See 2 more Smart Citations
“…However, brain lithium levels ( Figure 1b) were significantly different among groups: F(2, 23) = 62.53, p < 0.0001. This is consistent with the finding from numerous groups that establishment of steady-state brain lithium levels in the rodent brain lags behind serum lithium levels (Ghoshdastidar et al, 1989;Gould et al, 2007b;Morrison et al, 1971). Bersudsky and colleagues recently reported that the effect of lithium in the FST after long-term treatment requires serum levels above 0.8 mM (Bersudsky et al, 2007).…”
Section: Experiments 1: Determination Of Brain and Serum Lithium Levelssupporting
confidence: 91%
“…Whole brain lithium levels (mmol/kg wet weight) were determined following polytron homogenization of the entire brain (Kinematica AG Model PCU 11, Littau, Switzerland) in 3 volumes of 0.5 N trichloroacetic acid (Hamburger-Bar et al, 1986) (Gould et al, 2007b). Following centrifugation, lithium assays were performed on the supernatant with a digital flame photometer (Cole-Palmer Model 2655-00, Chicago, Illinois).…”
Section: Lithium Concentration Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…One such model is methamphetamine-induced hyperlocomotion/mania, which is known to be responsive to lithium in many mouse strains (37). Interestingly, although no molecular mechanisms have been offered, methamphetamine has also been suspected of modulating GSK3β signaling in the nucleus accumbens (38), impinging on dendritic spine formation (39) and effecting Ca 2+ channel expression (40).…”
Section: Resultsmentioning
confidence: 99%
“…That work was subsequently extended to look at the gene expression changes in blood from the animals on the different treatments, as a way of identifying brain-blood biomarkers [Le-Niculescu et al, 2009b]. Niculescu et al, 2008Niculescu et al, , 2011b Nile grass rat [Ashkenazy-Frolinger et al, 2010] Methamphetamine [Niculescu et al, 2000;Macedo et al, 2013] Learned helplessness [Mingmalairak et al, 2010] CLOCK [Roybal et al, 2007;Mukherjee et al, 2010;Arey et al, 2013] Flinders Sensitive Line (FSL) rats [Malkesman and Weller, 2009] Methamphetamine/valproate [Ogden et al, 2004] Isolation housing [Le-Niculescu et al, 2008;Niwa et al, 2013] CTNNB1 [Gould et al, 2008] Wistar Kyoto (WKY) rats [Will et al, 2003;Malkesman and Weller, 2009] Amphetamine-chlordiazepoxide [Kelly et al, 2009] Forced swim test [Le-Niculescu et al, 2008] POLG [Kasahara et al, 2006;Kubota et al, 2010] Madison (MSN) [Saul et al, 2012] Lithium [Gould et al, 2007;Johnson et al, 2009;Kovacsics and Gould, 2010] Tail suspension test [Le-Niculescu et al, 2008] HINT1 [Barbier and Wang, 2009] Other mood stabilizers: Lamotrigene [Li et al, 2010], Topiramate [Bourin et al, 2009] Restraint stress [Johnson et al, 2009;Koo et al, 2010] GRIN2A [Taniguchi et al, 2009] Ouabain [Herman et al, 2007] Shock-induced aggression …”
Section: Animal Modelsmentioning
confidence: 99%